(untitled) (Bangladesh Journal of Zoology, 2025)
Breeding activities are important behaviour in bird life. A study on the Lesser Adjutant (Leptoptilos javanicus) was conducted between February 2020 and April 2024 in northern and northeastern Bangladesh to determine the nesting sites, breeding biology and threats. We identified two nesting sites: one in Haripur, Thakurgaon. A new breeding site in Godagari, Rajshahi was detected where two incomplete nests were found, but no eggs were laid, and six adult Lesser Adjutants were present in the nesting tree. Six occupied nests were counted during 2023 from the known breeding site in Singhari, Haripur. Both the nesting tree was Shimul (Bombax ceiba), and the nesting height was 38 m in Godagari and 22-25 m (mean 23.5 ± 0.95 m, N=6) at Singhari. Nest construction requires approximately 12 to 18 days (mean 14.83 ± 2.03 days, N=6) and laid two to three eggs (mean 2.33± 0.51 eggs, N = 6). Both male and female bird incubated the eggs, and incubation period was varied from 30 to 33 days (mean 31.33± 1.10 days, N = 6). The nesting success was 100%, and the incubation success was 78.57%; 1-2 nestlings per nest (mean 1.83± 0.41 nestlings, N = 6). Major threats include the cutting of nesting trees and hunting birds by the local people. Parents cared for the hatchlings, feeding them regurgitated fishes and other aquatic prey organisms. In 2023, fledglings survived 63.64%, and breeding success was 50% in relation to number of eggs laid. In 2022, fledgling survival was 92.85% in relation to nestling; and in 2021 it was 71.42%. After 60 to 70 days, they leave the nest to practice flying while their parents continue to guide them until they can survive independently. This study indicated that Lesser Adjutant successful can breed in Bangladesh if nesting trees are available. Bangladesh J. Zool. 52(3): 225-235, 2024